2023
DOI: 10.1002/fsn3.3181
|View full text |Cite
|
Sign up to set email alerts
|

Identification of volatile and nonvolatile compounds in Citri Reticulatae Pericarpium Viride using GC–MS, UPLC‐Q‐Exactive Orbitrap‐MS, and HPLC‐PDA

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In contrast, several organic acids and fatty acids showed decreased levels in HLB-affected 9-year PCRC as compared to healthy PCRC. None of the depleted organic acids in the 9-year PCRC were identified as the key compounds, according to previous studies [ 26 , 39 ]. This indicated that most key organic acids that contributed to the bioactivity of PCRC were not influenced by HLB.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…In contrast, several organic acids and fatty acids showed decreased levels in HLB-affected 9-year PCRC as compared to healthy PCRC. None of the depleted organic acids in the 9-year PCRC were identified as the key compounds, according to previous studies [ 26 , 39 ]. This indicated that most key organic acids that contributed to the bioactivity of PCRC were not influenced by HLB.…”
Section: Discussionmentioning
confidence: 71%
“…Terpenoids were the main volatile compounds identified in the essential oil of PCRC and possessed various biological activities, such as antioxidant, antimicrobial, anticancer, and antiallergic [ 25 , 26 ]. Most of the accumulated HLB-affected PCRC had been found to display numerous pharmacological activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations